Financing of Micro, Small, and Medium Enterprises by Banks: A Case Study of Punjab National Bank (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of India's economy, contributing significantly to GDP and employment. This study explores the role of Punjab National Bank (PNB) in financing MSMEs, examining credit accessibility, repayment behavior, and challenges faced by MSME borrowers. A chi-square test is conducted to analyze the association between MSME category (Micro, Small, or Medium) and loan approval rates. The findings reveal that while PNB plays a pivotal role in supporting MSMEs, challenges like delayed approvals and inadequate credit persist.